Positive Working Relationships: How Closeness to the Healthcare System Affects Healthcare Workers’ Trust - Nafilah Nahar Alotaibi; Ahmed Nasser Alghashmari; Musnid Tawab Almutiri; Alanoud Mohammad Alotaibi; Fozeya Elwan Hdroog Almonteshery; Shadia Musa Mohammeid Sweid; Ana Nasser Ahmad Al Adawi; Azhar Mohammed Mohduly Ashawi; Manal Muhammad Abdullah Ageeli; Shefa Mousa Mohammed Sweed; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Trust is essential for effective collaboration among healthcare workers, which is vital for improving patient outcomes, especially in the care of complex conditions like diabetic foot ulcers. As healthcare teams increasingly operate in distributed settings, understanding how trust is built between healthcare worker pairs, both co-located and distributed, is crucial for enhancing teamwork. Methods: This study investigated the trust-building process among healthcare workers involved in the care of diabetic foot ulcer patients. A total of 39 healthcare professionals, including primary care providers, specialists, and administrative staff, were interviewed across rural and urban settings. Semi-structured interviews focused on trust-building mechanisms, with particular attention to co-location and shared electronic health records (EHRs) as factors influencing trust. Data were analyzed using directed content analysis, with an inductive approach applied to explore trust-related themes. Results: Findings revealed that trust develops gradually through introductions, communication, and collaboration, with proximity playing a significant role in these stages. Co-located pairs or those sharing an EHR found it easier to establish trust, with informal, spontaneous communication enhancing relationships. In contrast, distributed pairs faced challenges in communication, which complicated trust-building. However, despite the difficulties, trust was still established through timely communication and mutual respect for professional boundaries. Conclusion: The proximity of healthcare worker pairs, whether through co-location or shared EHR systems, is a key factor in developing trust and facilitating effective collaboration. These findings suggest that improving proximity and communication mechanisms, particularly in distributed settings, can enhance teamwork, leading to better patient care and outcomes in complex cases like diabetic foot ulcers.